PENGARUH PEMBERDAYAAN SDM DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI (STUDI KASUS PADA KANTOR DINAS PENDIDIKAN PEMUDA DAN OLAH RAGA SUMATERA UTARA) - Siti khadijah; Hardi Mulyono; Abd. Rasyid Syamsuri (LPPM Universitas Labuhanbatu, 2021)
This study aims to analyze the effect of empowering human resources and individual characteristics on employee performance (a case study at the North Sumatra Youth and Sports Office). The method used in this research is quantitative. This research was conducted at the Department of Youth and Sports of North Sumatra, which is located at Jl. Williem Iskandar No.9, Memories Baru, Kec. Percut Sei Tuan, Deli Serdang Regency, North Sumatra. The research method used in this study is the method of observation, documentation and questionnaires using a Likert scale. The population in this study amounted to 168, in determining the sample taken using the Slovin formula, and using probability sampling technique, namely proportional stratified random sampling, namely sampling that provides equal opportunities for each element (member) of the population to be sampled. selected as a member of the sample, the sample in this study amounted to 118 samples. The analytical method used is the multiple linear regression method using the SPSS program. The results of the research with a partial test that HR Empowerment has a t value of 7.484 > 1.6578, so it can be concluded that the HR Empowerment variable has a positive and significant effect on the Performance of the Youth and Sports Office of North Sumatra. Individual Characteristics has a t-count value of 7.844 > 1.6578, so it can be concluded that individual characteristics have a positive and significant effect on the performance of the Youth and Sports Office of Sumatra Province. Based on the results of the F test (simultaneous) that simultaneously HR Empowerment and Individual Characteristics have a positive and significant effect on employee performance. The results of the analysis of the coefficient of determination (R2) show that HR Empowerment and Individual Characteristics have an influence on employee performance of 62.7%, while the remaining 37.3% is influenced by other variables not examined in this study.